Practical cloud security : a guide for secure design and deployment - Dotson, Chris
"With their rapidly changing architecture and API-driven automation, cloud platforms come with unique security challenges and opportunities. This hands-on book guides you through security best practices for multivendor cloud environments, whether your company plans to move legacy on-premises projects to the cloud or build a new infrastructure from the ground up. Developers, IT architects, and security professionals will learn cloud-specific techniques for securing popular cloud platforms such as Amazon Web Services, Microsoft Azure, and IBM Cloud. Chris Dotson--an IBM senior technical staff member--shows you how to establish data asset management, identity and access management, vulnerability management, network security, and incident response in your cloud environment."--Back cover.